E-088 Psychological impact of pulsatile tinnitus in the US population. (22nd July 2019) - Smith, E; Amans, M; Meisel, K; McCoy, D
Abstract : Introduction/Purpose: Pulsatile tinnitus (PT) is the auditory perception of a rhythmic, cardiac-synchronized, 'whooshing' type of sound in the absence of an external source that affects 3–5 million Americans. In addition, several of the anomalies that cause PT can have serious sequelae such as ischemic stroke, blindness, or intracranial hemorrhage. In addition, it is common for patients to describe an inability to continue to function in their families and in society due to the psychological impact of PT (which may be depression, anxiety, or a combination). In our experience, treating the underlying cause of PT not only mitigates the risks of the vascular anomaly, but also the patients' psychiatric illness. However, the prevalence of depression and anxiety in the PT population is unknown. The purpose of this study was to quantify the prevalence of depression and anxiety in the United States PT population, as well as identify relationships between patient characteristics, effects of PT on various aspects of life, depression, and anxiety. Materials and methods: Local IRB approval was obtained to survey the pulsatile tinnitus community. The survey used the validated Tinnitus Functional Index (TFI) to determine the severity of the PT condition (intrusive, sense of control, cognitive, sleep, auditory, relaxation, quality of life, emotional). In addition, the PHQ-9 and GAD-7 was used to obtain the prevalence of concurrent depression and anxiety, respectively. Logistic multiple regression analysis was performed for determining the associations of clinical and demographic variables with TFI total score. Additionally, PHQ9 and GAD7 scores (binarized to indicate depression/anxiety) were modeled with TFI total score as the main exposure variable with possible covariates in multiple regression modeling. Results: The prevalence of moderate to severe depression in the PT population was 41.2%. Multiple regression to predict PHQ-9 diagnosed depression based on TFI total score, clinical variables, and demographics showed a significant odds ratio for TFI (OR: 1.084, CI: 1.065–1.096, p<0.001). The increase of sub-scores for quality of life interference and emotionality showed significant increases in odds for depression (OR: 1.031, CI: 1.016–1.046, p<0.001; OR: 1.042, CI: 1.027–1.058, p<0.001). Unemployed vs. employed and laterality were also associated with an increased odds of depression, and age with decreased odds while controlling for tinnitus score. Moderate to severe anxiety was present in 43.1%. Multiple regression analysis showed TFI was associated with increased of odds for anxiety (OR: 1.056, CI: 1.043–1.070, p<0.001). TFI sub-scores for emotionality (OR: 1.043, p<0.001), quality of life (OR: 1.019, p<0.005), and cognitive interferences (OR: 0.983, p = 0.015) were found to be significantly associated with anxiety scores. Conclusion: The estimated prevalence of moderate to severe depression and anxiety in the US PT population is 41.2% and 43.1%, respectively, which is higher than a recent systematic review of depression in tinnitus suggesting a depression prevalence of 33%. TFI score was significantly associated with both depression and anxiety. Similarly, more granular sub-scores of the TFI elucidate how PT affects the psychological health of these patients. Disclosures: E. Smith: None. M. Amans: 1; C; This work was funded by an NIH grant. 2; C; Consultant for Covidien and Stryker. K. Meisel: None. D. McCoy: None.